Analysis of the Physical and Colors Addition Characteristics in the Particles with Bixa Orellana and Blue Textile Dye for Feasibility of Production of the Oriented Particleboard - Moizes, Fabio A.; Valarelli, Ivaldo [UNESP]; Silva, João Carlos R. Plácido (Springer Nature, 2023)
Oriented strand board (OSB) due to its physical and mechanical characteristics represent the evolution of the plywood laminates and correspond to the higher growth in the production of wood panels in recent years. This study makes possible the production of panels of type Oriented Strand Board using bamboo particles classified as thin flakes, called “flakes”, with natural finish, dyed before pressing the panel with the Bixa Orellana plant, popularly known in Brazil as annatto, and dyed blue textile dye, stabilized in an air-conditioned greenhouse with the addition of the castor oil resin in the panel composition. The panel structure was divided into five layers with smaller particles randomly distributed on the two surfaces, and the three layers pellets with larger particles distributed longitudinally, transversely, longitudinally. The result of the conformation and pressing of the panel was due to the selection of particles in vibrating sieve, resin-mixing drum, forming mattress and hydraulic press. The production of oriented particleboard has been increasing in recent years due to the mechanical characteristics similar to the compensated panels, however, there are few studies for a sustainable production using renewable natural materials and with the minimum of manufacturing processes. The study proposes the sustainable production, with rapidity in the processing and obtaining of the raw material, pressing of the panels of the type OSB of Bamboo with treatment and previous dyeing of the particles with equivalent physical or mechanical performance manufactured by the companies of the sector of wood.
Keywords: Bambusa vulgaris; Environmental sustainability; Manufacturing process; Oriented strand board; Particle dyeing